ANALISA VARIASI TEKANAN, TEMPERATURE, UKURAN RUNNER TERHADAP FILLING TIME OPTIMAL PADA INJEKSI MOLDING - Ellysa Kusuma Laksanawati (Universitas Muhammadiyah Tangerang, 2021)
AbstractPlastic based packaging systems for food box lid products receive special attention from manufacturers and the most common process is injection molding. This study aims to analyze the effect of variations in pressure, temperature, and runner size on filling time in the injection molding process for food box products using Autodesk Inventor 2015 software in order to obtain the optimal filling time. Experiments in the form of simulations were carried out by entering data on variations in pressure, temperature, and runner size. The results of this study obtained the optimal filling time at the melting temperature setting of 220℃, injection pressure of 90 Mpa, mold temperature of 40℃, and runner diameter of 6 mm. The optimal type of gate tunnel and runner circle type has a filling time analysis result of 0.34 seconds. Defects that occur during the injection molding simulation process are weld lines, air traps and short-shots. Based on these problems, a mold unit was designed with a two plate mold system type. Keywords: Plastic, Injection Molding, Experiment, Lid Food Box, Inventor, Mold.